2003
DOI: 10.1093/nar/gkg299
|View full text |Cite
|
Sign up to set email alerts
|

3'-Exonuclease resistance of DNA oligodeoxynucleotides containing O6-[4-oxo-4-(3-pyridyl)butyl]guanine

Abstract: Tobacco-specific nitrosamine, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), is a chemical carcinogen thought to be involved in the initiation of lung cancer in smokers. NNK is metabolically activated to methylating and pyridyloxobutylating species that form promutagenic adducts with DNA nucleobases, e.g. O(6)-[4-oxo-4-(3-pyridyl)butyl]guanine (O(6)-POB-dG). O(6)-POB-dG is a strongly mispairing DNA lesion capable of inducing both G-->A and G-->T base changes, suggesting its importance in NNK mutagenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
5
18
0
Order By: Relevance
“…Further characterization by enzymatic digestion followed by RP‐HPLC showed the appearance of a new peak with retentions of 9.2 min and 14.7 min for the butylene and heptylene 2′‐deoxyguanosine adducts, respectively (see the Supporting Information). The retention of these dimers was significantly lower compared with those observed for the enzymatic digestion of GG4 and GG7 (16.4 min and 24.8 min), respectively, suggesting incomplete digestion near the cross‐linked site, as previously observed for other DNA modifications …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Further characterization by enzymatic digestion followed by RP‐HPLC showed the appearance of a new peak with retentions of 9.2 min and 14.7 min for the butylene and heptylene 2′‐deoxyguanosine adducts, respectively (see the Supporting Information). The retention of these dimers was significantly lower compared with those observed for the enzymatic digestion of GG4 and GG7 (16.4 min and 24.8 min), respectively, suggesting incomplete digestion near the cross‐linked site, as previously observed for other DNA modifications …”
Section: Resultssupporting
confidence: 55%
“…The retention of these dimers was significantly lower compared with those observed for the enzymatic digestion of GG4 and GG7 (16.4 mina nd 24.8 min), [28] respectively,s uggesting incomplete digestion near the cross-linked site, as previously observed for other DNA modifications. [33,34] UV thermaldenaturation and circular dichroisms tudies of IaCL DNA…”
Section: Synthesis and Characterization Of Iacl Dnamentioning
confidence: 99%
“…From these results, it was found that incorporation of Na‐N O and Im‐O N units into ODNs improved the resistance to SVPD digestion with an increasing number of these units despite their possessing a natural phosphodiester linkage. Thus far, a number of chemically modified ODNs have been developed, and their SVPD resistance has been discussed 11. The resistance of these ODNs to SVPD digestion has been attributed to a variety of factors, including steric hindrance, interference with the metal ion binding in the exonuclease active site, and altered conformation of the phosphate‐sugar backbone.…”
Section: Resultsmentioning
confidence: 99%
“…First, a different enzymatic hydrolysis procedure was used in the previous study. The DNA may have been digested incompletely due to resistance of O 6 -POB-dGuo to the enzymatic activity of snake venom phosphodiesterase I (23). Second, the previous study did not use deuterated internal standards for each adduct.…”
Section: Discussionmentioning
confidence: 99%